The Use of AI ChatBots to Increase Student Enthusiasm for Writing Arabic Theses at Mataram Islamic University - Husnan Hanan; Nasarudin Nasarudin; Ahmad Helwani (Journal of Arabic Language Teaching, 2025)
This study aims to examine the relationship between the use of AI chatbots and students' enthusiasm for writing Arabic theses at UMMAT and UIN Mataram, as well as to compare the level of enthusiasm between students from the two institutions. The research employed a quantitative correlational and comparative approach, using a questionnaire as the primary instrument. Data were analysed using the product-moment correlation formula and an independent-samples t-test. The findings show a highly significant relationship between the use of AI chatbots and students' enthusiasm for writing Arabic theses at both universities. Linear regression analysis indicates a positive contribution, with a significance value of 0.000 and a beta coefficient of 0.912, suggesting that higher use of AI is associated with higher levels of enthusiasm. The t-test results reveal a significant difference between the two institutions (sig. 0.001), with UIN Mataram students demonstrating greater enthusiasm than those at UMMAT. These differences, while not part of the measured variables, may be interpreted as being influenced by contextual factors such as academic environment, facilities, institutional policies, and academic culture. In conclusion, the use of AI chatbots has a strong positive association with students' enthusiasm for thesis writing, and enthusiasm levels differ significantly between institutions, with contextual interpretations provided for the observed patterns.